2020
DOI: 10.1002/mame.201900835
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Strategy to Achieve Ultralow Electrical Percolation Threshold with CNTs Anchoring at the Interface of PVDF/PS Bi‐Continuous Structures to Form an Interfacial Conductive Layer

Abstract: Conductive composites based on polymers and conductive nanofillers are widely studied as a promising material. The rational design of 3D conductive networks in composites is crucial to improve their electrical conductivity and reduce the dosage of nanofillers. Herein, poly(vinylidene fluoride) (PVDF) and polystyrene (PS) bi-continuous structures with modified carbon nanotubes (CNTs) tailored to anchor at the interface are designed to achieve an ultralow electrical percolation threshold because of the formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…Therefore, the percolation threshold ϕ c II was estimated to be 0.02, which was considerably smaller than ϕ c I . Generally, anisotropic fillers with small diameters and high aspect ratios, such as CNTs, are reported to exhibit a low percolation threshold from 0.08 to 3 wt% in CPC with a blended matrix [8][9][10][11][12][13][14]. Furthermore, in our previous studies on composite films of P3HT nanofibers in polymethacrylate (PMMA), a significant amount of conductivity was measured for the ratio of P3HT/PMMA at approximately 5 wt% [28].…”
Section: Electrical Conductivity Of Pb/peg Blends Loaded With P3ht Namentioning
confidence: 90%
See 2 more Smart Citations
“…Therefore, the percolation threshold ϕ c II was estimated to be 0.02, which was considerably smaller than ϕ c I . Generally, anisotropic fillers with small diameters and high aspect ratios, such as CNTs, are reported to exhibit a low percolation threshold from 0.08 to 3 wt% in CPC with a blended matrix [8][9][10][11][12][13][14]. Furthermore, in our previous studies on composite films of P3HT nanofibers in polymethacrylate (PMMA), a significant amount of conductivity was measured for the ratio of P3HT/PMMA at approximately 5 wt% [28].…”
Section: Electrical Conductivity Of Pb/peg Blends Loaded With P3ht Namentioning
confidence: 90%
“…Conductive polymer composites (CPC) that comprise immiscible polymer blends and conductive fillers are novel composite materials, featuring advantages of both polymer blends and conductive fillers. Generally, by loading conductive fillers such as carbon black (CB) [1][2][3][4][5][6][7][8], carbon nanotubes (CNTs) [9][10][11][12][13][14], and graphene [5], it was reported that the resultant mechanical strength and electrical properties can be drastically modified. In particular, the conductivity can be changed from that of an insulator to that of a conductor by increasing the amount of fillers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[96][97][98] The selective distribution of the filler particles in the interfacial region or in a single phase of co-continuous polymeric blends (generating a network of conductive particles) and the formation of a conductive network of filler-rich polymeric phase inside the composite is designated as double percolation. [99] This phenomenon was firstly described by Sumita et al [100] for HDPE/PP and PMMA/PP blend-based CB composites. [101] Figure 8 shows the effect of the selective localization of carbon filler particles on the electrical percolation threshold of blend-based polymer composites.…”
Section: Morphology Of the Polymeric Matrix On Blendsmentioning
confidence: 79%
“…Yang et al [99] produced PVDF/ polystyrene (PS) (45/55) blends with different volume content (0.05, 0.09, 0.18, and 0.36 vol%) of pristine CNT or CNT grafted with PMMA chains (CNTs-PMMA). The authors verified that non-modified CNT was selectively distributed on the PS phase of PVDF/PS blend.…”
Section: Morphology Of the Polymeric Matrix On Blendsmentioning
confidence: 99%